Prywatne jest polityczne, czyli o publicystyce Ireny Krzywickiej - Pietruszewski, Filip (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
In 1930s Irena Krzywicka has been writing texts, which content is close to ideological assumptions of cultural feminism. In her work, she fought for the equal rights for women in such areas as erotic custom, divorces and intentional motherhood. On the basis of various I. Krzywicka’s publications: columns, reports, books and theatrical plays reviews, diagnosis and suggestions about social reforms postulated by publicist were described. Due to volume limits, only Krzywicka’s thoughts regarding social meaning of women are presented in this article. Furthermore, it contains genealogy of Krzywicka’s outlook and attempt to review her postulates in XXI century.